Proton Pump Inhibitors and Cardiovascular Disease: A Review of Clinical Evidence and Biological Mechanisms - Hassan, Syed Adeel; Farooque, Umar; Jamal, Somia; Yasmin, Farah; Kumar, Naresh; Hussain, Tooba; Girdhari, Komal; Ezeh, Jude; Sheikh, Fahad Nawaz; Choudhry, Ali; Naeem, Ifrah; Khan, Malik Muhammad Uzair (Cardiology and Cardiovascular Medicine, 2020)
Proton pump inhibitors (PPIs) are amongst the most commonly prescribed medications in the clinical setting. They are commonly used for the treatment of gastroesophageal reflux disease and are readily available over the counter. However, their irrational long term use has been repeatedly discouraged. PPIs are highly lipophilic and may adversely affect multiple physiological pathways of various organs. Over the past few decades, multiple clinical studies have linked PPI use with an increased risk of cardiovascular disease. In this review, we discuss the PPI-induced pathophysiological mechanisms that contribute to cardiovascular disease. Furthermore, we highlight clinical evidence that associates PPI use with an increased risk for various cardiovascular manifestations.